Teaching Singing in Primary Schools Based on Art Curriculum Standards for Compulsory Education (2022), China - Yuanshan, Li; Pattananon, Nicha; Sribandasakwacharaporn, Narongsak (Journal of Modern Learning Development, 2023)
According to the "Art Curriculum Standards for Compulsory Education" (2022 edition), the training objectives of music teaching in primary schools in China take the overall training objectives of primary school compulsory education as the theme, emphasizing the aesthetic function and educational role of music education. Students learn and participate in various artistic practice activities through music courses, explore, discover and appreciate music’s artistic charm, cultivate lasting interest in music, self-cultivation of beauty, the harmony of body and mind, edify sentiment, and perfect personality. Learn and master the necessary basic knowledge and skills of music, expand the cultural vision, develop the ability of music hearing and appreciation, performance and creation, and form basic music literacy. Enrich emotional experience, cultivate good aesthetic taste and positive attitude towards life, and promote the healthy development of body and mind. This article presented the teaching of singing in primary schools based on art curriculum standards for compulsory education (2022) in China.